Reduction of spinal PGE2 concentrations prevents swim stress-induced thermal hyperalgesia. (30th March 2015) - Guevara, Coram; Fernandez, Ana Cristina; Cardenas, Ricardo; Suarez-Roca, Heberto
Highlights: COX inhibitors prevented stress-induced thermal hyperalgesia and increased escape behavior. Serum corticosterone was augmented in forced-swim animals. COX inhibitors (ketoprofen and meloxicam) diminished serum corticosterone levels. Spinal PGE2 levels were higher in forced-swim formalin injected animals. Ketoprofen and meloxicam blocked the increase in spinal PGE2 . Abstract: We evaluated the association between spinal PGE2 and thermal hyperalgesia following repeated stress. Thermal nociception was determined in male Sprague–Dawley rats using the hot-plate test, before and after forced-swimming; non-conditioned rats served as controls. Animals were pretreated with ketoprofen or meloxicam, preferential COX-1 and COX-2 inhibitors, respectively. After the second hot-plate test, we measured serum corticosterone (stress marker), and lumbar spinal PGE2 (neuroinflammation marker) under peripheral inflammation (1% formalin plantar injection). Stressed rats displayed response latencies 40% shorter and inflammatory spinal PGE2 levels 95% higher than controls. Pretreatment with ketoprofen or meloxicam prevented hyperalgesia and elevation of spinal PGE2, increasing the escape behavior time during forced swimming 95% respect to saline-treated rats. Corticosterone levels in stressed rats were 97% higher than controls; COX inhibitors reduced them by 84%. PGE2 could participate in stress-induced hyperalgesia, learned helplessness, and corticosterone production, supporting the use of non-steroidal anti-inflammatory drugs (NSAIDs) for persistent pain associated with chronic stress and depression.